Evans Syndrome in Childhood: Long Term Follow-Up and the Evolution in Primary Immunodeficiency or Rheumatological Disease - Rivalta, Beatrice; Zama, Daniele; Pancaldi, Giovanni; Facchini, Elena; Cantarini, Maria Elena; Miniaci, Angela; Prete, Arcangelo; Pession, Andrea (Frontiers in Pediatrics, 2019)
Evans syndrome (ES) is a rare but challenging condition, characterized by recurrent and refractory cytopenia episodes. Recent discoveries highlight that an appropriate diagnostic workup is fundamental to identify an underlying immune dysregulation, as a primary immunodeficiencies or a rheumatological disease. Here we describe the clinical features and laboratory results of 12 pediatric patients affected by ES referred to the Pediatric Onco-Hematology Unit of Bologna. Patients experienced a median of four acute episodes of cytopenia with 9 years as median age at the onset of symptoms. In 8/12 (67%) patients an underlying etiology, primary immunodeficiencies or rheumatological disease was identified. In 4/12 children other immune manifestations were associated (Thyroiditis, Celiac disease, Psoriasis, Vitiligo, Myositis, Membranoproliferative Glomerulonephritis). ES remained the primary diagnosis in four patients (33%). At a median follow-up time of four years, 5/12 (42%) patients revealed a chronic ITP, partially responsive to second line therapy. Immunoglobulin Replacement Therapy was effective with a good hematological values control in three patients with a secondary ES (ALPS, CVID and a patient with Rubinstein Taybi Syndrome and a progressive severe B cell deficiency with hypogammaglobulinemia). Our experience highlights that, in pediatric patients, ES is often only the first manifestation of an immunological or rheumatological disease, especially when cytopenias are persistent-resistant to therapy, with an early-onset or when are associated with lymphadenopathy.